Listeria monocytogenes Establishes Commensalism in Germ-Free Mice Through the Reversible Downregulation of Virulence Gene Expression - Cho, Kyungjin; Spasova, Darina; Hong, Sung-Wook; O, Eunju; Surh, Charles D.; Im, Sin-Hyeog; Kim, Kwang Soon (Frontiers in Immunology, 2021)
The intestine harbors a complex community of bacterial species collectively known as commensal microbiota. Specific species of resident bacteria, as known as pathobiont, have pathogenic potential and can induce apparent damage to the host and intestinal inflammation in a certain condition. However, the host immune factors that permit its commensalism under steady state conditions are not clearly understood. Here, we studied the gut fitness of Listeria monocytogenes by using germ-free (GF) mice orally infected with this food-borne pathogen. L. monocytogenes persistently exists in the gut of GF mice without inducing chronic immunopathology. L. monocytogenes at the late phase of infection is not capable of infiltrating through the intestinal barrier. L. monocytogenes established the commensalism through the reversible down regulation of virulence gene expression. CD8+ T cells were found to be sufficient for the commensalism of L. monocytogenes. CD8+ T cells responding to L. monocytogenes contributed to the down-regulation of virulence gene expression. Our data provide important insights into the host-microbe interaction and have implications for developing therapeutics against immune disorders induced by intestinal pathogens or pathobionts.